ANALISIS PENYALURAN DANA ZAKAT OLEH BADAN BAITUL MAL DAN FAKTOR INPUT TERHADAP TINGKAT PRODUKSI DAN PENGANGGURAN DI KABUPATEN ACEH UTARA - Mukhtasar Mukhtasar (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2017)
The purpose of this research is to know about the impact of the flow of incoming capital in indonesia’s moneter condition. Using moneter theory and from the previous research, then the variable we observed in this research is the flow of incoming capital formed in production (PRD), unemployment (PGG), education of labor (PDDTK), amount of labor (JTK), zakat (ZKT). This research uses time series data analyzed by using vector autogression method (VAR). All the variable and contribute in long, middle, and short term. Keyword : Production (PRD), Unemployment(PGG), Enducation of Labor (PDDKT), Amount of Labor (JKT), Zakat(ZKT)